PEMASARAN SYARIAH PADA LEMBAGA KEUANGAN MIKRO SYARIAH - adinugraha, hendri hermawan (IAIN Tulungagung, 2017)
The rise of sharia finance industry that used âsharia brandingâ such as sharia banking, sharia mini market, sharia hotel, until sharia franchise resulted in conventional institutions are also diversifying sharia-compliant. Ideally this should be balanced by the application of such management is based on sharia like sharia marketing, but in reality many of them are not implementing it yet. Based on the above reasons, this research aims to understand the concept and implementation of sharia marketing at Micro Islamic Financial Institutions (Puskopsyah DIY) comprehensively. This study used a type of field research that is descriptive analytical. This study is also equipped with library research. Data collection techniques using triangulation method, while the data analysis techniques using taxonomic analysis with interactive model. The survey results revealed that implementation of sharia marketing concept in Puskopsyah DIY was good enough though not all aspects of running perfectly. For example, the facts on the ground show that not all product marketing process carried out by the prevailing fatwa supervised and issued by the Sharia Supervisory Board. Keywords: Sharia, Marketing, and Puskopsyah DIY.